2017
DOI: 10.1093/icvts/ivx168
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral bidirectional Glenn: outcome of off-pump technique

Abstract: Off-pump b-BDG can be conducted safely, with a uniform anastomosis that allows a good central pulmonary artery growth for subsequent Fontan completion. Moreover, avoiding the use of cardiopulmonary bypass is more economic and less hazardous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The BDG procedure done without CPB is an economical and safe procedure. 6 Our technique of performing BDG using Kehr's T tube involves neither any suture over SVC for cannulation nor the need of CPB equipments and hence is safe for short term as well as long term and is much more economical. This technique is quite challenging and difficult to start with as we felt but, once performed, will boost confidence for many more cases.…”
Section: Discussionmentioning
confidence: 99%
“…The BDG procedure done without CPB is an economical and safe procedure. 6 Our technique of performing BDG using Kehr's T tube involves neither any suture over SVC for cannulation nor the need of CPB equipments and hence is safe for short term as well as long term and is much more economical. This technique is quite challenging and difficult to start with as we felt but, once performed, will boost confidence for many more cases.…”
Section: Discussionmentioning
confidence: 99%
“…The Glenn procedure as the first palliative procedure reportedly has good results. 5,18 Thus, it can be an option for our patients.…”
Section: Commentmentioning
confidence: 99%
“…The care of patients with congenital heart disease (CHD) in low-income countries has improved, leading to increased survival and better quality of life. [1][2][3][4][5] Despite this progress, the postoperative care and mortality and morbidity rates of complex CHD remain challenging. 1,3,4 Single ventricle physiology, one of the main complex CHD types, requires early detection and referral to a pediatric cardiac center.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have shown bSCPA to be a risk factor for thrombus formation and unfavorable alterations in PA growth [3], while others have directly contradicted this and shown no such risk increase [4]. Some have shown bSCPA to be safe with subsequent Fontan success [4,5], while others have shown that bSCPA patients have higher rates of post-operative complications, Fontan failure, and early mortality when compared to uSCPA patients [6]. There are conflicting data on whether bSCPA patients have worse outcomes than uSCPA patients, although many factors and hypotheses have been proposed [3,4,6,7].…”
Section: Introductionmentioning
confidence: 99%